Board composition and performance in Spanish non-listed family firms: The influence of type of directors and CEO duality - Maria Katiuska Cabrera-Suárez; Josefa D. Martín-Santana (BRQ Business Research Quarterly, 2015)
This study analyzes the effect that certain characteristics of board of directors in Spanish non-listed family firms have on performance. The results of a hierarchical regression analysis on a database of 544 firms show a negative effect of a higher proportion of executive directors and a positive effect of CEO duality. No effects were found in relation to the diversity of family directors (executive or non-executive). In relation to the effect of outside boards, the influence on performance is negative except when this variable was considered in interaction with CEO duality. In this case, the effect on performance was positive."
Keywords: 650; Private family firm; Board of directors; Performance